Great cloister : a lost Canterbury tale : a history of the Canterbury cloister, constructed 1408-14, with some account of the donors and their coats of arms - Fox, Paul A., (Archaeopress, 2020)
Great Cloister presents a new study of the heraldry, genealogy and history of the Canterbury Cathedral cloister. It is a comprehensive study of the monument, and it provides a detailed chronology as well as many new insights into the families who were donors. The monument is revealed to have been the personal project of Archbishop Thomas Arundel (d.1414), an individual closely connected with the overthrow of King Richard II. The work as a whole provides considerable insights into the revolution of 1399 and the troubled reign of Henry IV as seen through the lens of individual families. The cloister, as originally conceived, contained 856 heraldic shields, badges and devices of which 576 were unique. Some 365 families, principalities, religious foundations and other individuals both real and imagined were represented, some with more than one shield or device.